Substitusi Kebutuhan Nitrogen Tanaman Padi Sawah oleh Tumbuhan Air Azolla (Azolla pinnata) - Gunawan, Iwan; Kartina, Raida (Politeknik Negeri Lampung., 2012)
The research aims to study the ability of Azolla pinata in substituting nitrogen requirement of rice plants at a low dose of urea fertilizer. Factorial experiment arranged in randomized complete design (RCD) with four combinations of treatments and 6 replications. The first factor is the dose of urea with 2 dose level, ie, without urea (U0) and 100 kg urea ha-1 (U1). As a second factor is the provision of water plant Azolla pinnata with a degree without Azolla (A0) and Azolla 100 g m-2 (A1). The experimental results show that: (1) water plant azolla increased height, dry weight, productive tillers and dry weight of paddy rice crops, (2) Provision of a Urea increase high, dry weight, productive tillers and grain dry weight of rice plants, and (3) water plants azolla interacts with urea in increasing plant dry weight and grain dry weight of paddy. Keywords: Nitrogen, Rice, Azolla pinnata